A Life Lived Otherwise: Contingency and Necessity in an Interconnected World - Irving, Andrew (Anthropologica, 2018)
This article focuses on how people experience and understand their life and history in relation to the many other possible lives they could have ended up living. It argues that the alternative, imagined or virtual life courses that someone might have lived are an important moral framework for understanding and interpreting one’s social and material situation. Drawing on long-term fieldwork with a Ugandan family, the article considers how unfolding events continuously recast people’s existential life circumstances and their imagined alternatives. Using film and collaborative methods, it aims to offer an ethnographically grounded account of how people’s thoughts, dreams and imaginaries of a life lived otherwise are not immaterial fantasies or abstractions but are directly constitutive of people’s embodied experiences and responses to contingency in an interconnected world.